Notices of Ancient Gaelic Poems and Historical Fragments in a Ms. Volume (written in the years 1512 to 1529) called 'The Dean of Lismore's Book,' in the Advocates' Library (Proceedings of the Society of Antiquaries of Scotland, 1856)
This manuscript volume is thought to have belonged to James MacPherson, the author of the Ossian cycle. As such, only some of the contents of the manuscript have been examined for their historical accuracy. The article's author is confident that this manuscript is one of the earliest written examples of Scots Gaelic, despite the similarities between the manuscript’s contents and the contents of the Ossianic poems. The article also includes notes on the condition of the volume and its table of contents, as well as extracts of the poems themselves.